Radioatividade natural e composição das areias da Praia de Camburi (Vitória - ES, Brasil) - Sperandio, Etory Feller (2011)
According to the Organization for Economic Cooperation and Development (OECD)[32], Brazil, by the year 2009, had prospected only 25% of its territory and appearedin the first and sixth place as the holder of the world's largest deposits of thorium anduranium, respectively. Substantial portions of these elements are found in monazitesands and has been exploited commercially by the Nuclear Industries of Brazil (INB)from the 80's [31]. Recognizing the significant importance of the complex mineralmonazite growth in an incipient industry such as emerging countries, it is necessaryto map and assess the seasonal deposits of monazite occurring throughout theBrazilian coast. In this context, the Espírito Santo emerges with a jagged coastlinewith about 310 miles long and marked presence of sands rich in uranium (U), thorium(Th) and cerium (Ce) is still unexplored. This study aims to analyze the seasonaldeposits of monazite found in Camburi Beach in Vitoria, capital of Espirito Santo. Thecomplete survey of the dark spots, typical of monazite sands popularly known as,allowed to study the composition and behavior radiometric characteristics of theirplaces of occurrence by means of a temporal series. Several sand samples werecollected, cataloged and stored in bottles of high density polyethylene. Theradioactive counts, made from a Geiger-Müller counter, revealed marked differencesbetween the three sectors of the beach and stood out against Camburi the nearbybeaches. The magnetic separation of the sand fractions exhibited two distinct colorsand radiometric content. The composition of the whole grain was analyzed, then,using the technique of X-ray diffraction and resources of scanning electronmicroscopy (SEM).